Behçet's Disease with Multiorgan Infection: Alternative Treatment to Systemic Immunosuppressants - Dian Hasanah (Indonesian Journal of Rheumatology, 2020)
A B S T R A C T Background. Behçet's disease is a rare systemic autoimmune vasculitis. The presence of infection makes it difficult to manage. Case. Ms. X, 19 years old, complained of mouth and genitalia ulcers and joints pain. She had typhoid fever two months before; and a week after recovery, she experienced reddish skin lesions on her legs. Her condition was weak and the pain visual analog score (VAS) was 9/10. Multiple oral ulcers were found in her oral cavity and vulva. Her lungs were hypersonor. There were hyperpigmented maculae in her lower extremities. Her ankle joints were painful in passive and active movements. Blood leukocytes: 13,210/µl, urine leukocytes: 20-23/hpf, ANA, anti-dsDNA and Pathergy tests were negative. The diagnosis of Behçet's disease was based on multiple oral and genital ulcers, history of erythema nodosum and arthritis. The patient was treated with topical triamcinolone. Joint ulcers and pain worsened; so that intravenous methylprednisolone was administer. Two days later, the patient had cough and oxygen desaturation. Chest X-ray showed emphysematous lungs and pneumonia. Methylprednisolone was stopped, ceftriaxone and levofloxacin were given, treatment for ulcers and arthritis was replaced with colchicine and rebamipide. Sucralfate is given for gargle and applied to the genital ulcers. On the seventh day, the ulcers were greatly reduced, joint pain resolved, cough subsided and VAS became 2/10. On the twelfth day, the chest X-ray was normal and ulcers were healed, ankle pain was suffered again accompanied by swelling. The patient was treated with methylprednisolone and azathioprine. Discussion. Treatment for this disease is immunosuppressants. In severe conditions with infection, colchicine can be an alternative treatment. Adjuvant treatment are rebamipide and/or sucralfate. Emphysematous lungs can be caused by alpha-1 antitrypsin deficiency or pulmonary vasculitis, which can be manifested in autoimmune diseases. Emphysematous lungs, leads us to follow up on the development to other autoimmune disorders such as lupus. Conclusion. Behçet's disease with infection can be successfully managed with colchicine, rebamipide and sucralfate.